Wireless caching helper networks : ginibre point process modeling and analysis - Kong, Han-Bae (2020)
In this paper, we consider wireless caching helper networks (WCHNs) consisting of cache-enabled device-to-device (D2D) transmitters and caching helpers (CHs), which deliver data by exploiting cached contents. We consider two types of modes at a typical user, namely D2D and CH modes. In the D2D and CH modes, after requesting a content, the user receives the content from a D2D transmitter and a CH caching the content, respectively. In practical scenarios, to mitigate interference, the CHs may not be placed close to each other, and thus there exists a form of repulsion among the CHs' locations. In this context, we model the spatial distribution of the CHs as a β-Ginibre point processe, which reflects the repulsive behavior and contains the Poisson point process as a special case. Then, we provide analytical expressions for the coverage probabilities in the WCHNs.